Analisis Kinerja Keuangan Pada Usaha Dump Truck Di Desa Hatu, Maluku Tengah - Nathalia Putri Salamahu; Gesy Haumahu; Sri Rizki Wulandani Kssia; Gabriela Laura Tuankotta (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to analyze the system of financial performance in dump truck business in Hatu village. Assessment of a company's financial level can be done by analyzing the company's financial statements. To find out whether the company's financial condition is in good condition, various analyzes can be carried out, one of which is ratio analysis. The purpose of this study was to determine the financial performance of the Dump Truck business in terms of financial ratio analysis. The analytical method used is descriptive analysis using ratio measurements of liquidity, solvency, activity and profitability. Research data and information were obtained from the Dump Truck Business. Based on the liquidity ratio in terms of the current ratio, it shows that the current ratio in 2016 was 5.25%, 2017 was 4.81%, and 2018 was 3.83%. , This proves that DT's business is categorized in good standard criteria (liquid). From the solvency ratio in terms of the asset to debt ratio, it shows that the asset to debt ratio in 2016 was 12.3%, in 2017 it was 12.85%, and in 2018 it was 21.05%. This proves that DT's business is at very good standard criteria (solvable). Based on the profitability ratio in terms of return on equity, it shows that the return on equity in 2016 was 75.04%, in 2017 it was 59.16%, and in 2018 it was 63.28%. Thus, from a profitability standpoint, it shows that DT's business is at a good criterion standard.